A CARBON DOT-BASED CO-NANOZYME WITH ALKALINE PHOSPHATASE – MECHANISM AND APPLICATION - Fan, Haiyan; Dukenbayev, Kanat; Sun, Qinglei; Khamijan, Medina; Turdaliyev, Akhrorbek; Ysmaiyl, Alibek; Tassanbiyeva, Aigerim; Ma, Cuiping; Xie, Yingqiu (RSC Advances, 2021)
Elevated levels of alkaline phosphatase (ALP) are associated with bone metastasis, liver cancer, prostate cancer, breast cancer, and many other diseases or stem cell marker. It is therefore of great significance to quantitatively detect the ALP levels by a rapid, highly sensitive, and easy-to-use strip paper test. In the present work, we discovered an enhancement of ALP activity upon the addition of cauliflower-derived carbon dots (CFCDs), which can be applied as a sensor for ALP. The mixed ALP and CFCDs exhibited a typical Michaelis Menten mechanism with increased Vmax and reduced Km compared to ALP alone. High-Resolution Atomic Force Microscopy (HR-AFM) reveals the dimensions of ALP, the CFCDs, and the phosphatase substrate para-nitrophenyl phosphate (pNPP), as well as the potential interactions among them. The role of the CFCDs was identified as the addition of reaction centers to ALP; in other words, a competitive activator. Besides the improved kinetics, the yield of dephosphorylated product was also increased by at least twice upon the addition of CFCDs. Taking advantage of this effect, a portable CFCD-based paper strip assay was developed to achieve sensitive detection of abnormally elevated ALP levels and visualization of cancer stem cells or proteins by phosphatase-conjugated antibodies. Our findings show great promise for disease diagnosis and bioassays related to ALP enhancement that may be used for protein or cell detection.
Keywords: Type of access: Open Access; alkaline phosphatase; cancer